Teachers' and students' attitudes towards reading and writing: Do they correlate to students' achievement in English? - Titus Terver Udu (Universitas Syiah Kuala, 2021)
This survey tested the null hypothesis that teachers’ and students’ attitudes towards reading and writing do not simultaneously predict students’ achievement in the English language. The researcher utilized a sample of 38 teachers and 492 senior secondary school students from 12 schools in Benue State, Nigeria, for the study. The researcher developed and utilized the English Language Students’ Attitude Scale (ELSAS), English Language Teachers’ Attitude Scale (ELTAS), and Reading and Writing Achievement Test (RWAT) for data collection. An estimate of internal consistency was obtained through Cronbach’s Alpha and Kuder Richardson’s reliability methods and found to be 0.76 for ELSAS, 0.68 for ELTAS, and 0.81 for RWAT. Data analysis was by multiple regression statistics. The findings revealed that both English language teachers and students have a positive attitude towards reading and writing (F3, 492 = 0.160, p0.05) implying that teachers and students’ attitudes towards reading and writing jointly predicted students’ achievement in the English language in senior secondary schools. To conclude, learning would be facilitated if both teachers and students hold positive attitudes towards reading and writing, and this, in turn, could impact the students’ achievement in the English language. It was recommended that teachers should plan reading and writing instruction that can help students develop positive attitudes to these skills and parents should help in the development of these skills at home.